The dimeric conformation of PRRSV nsp1α is important for its ability to regulate viral RNA synthesis - Qingyu Li; Jingbo Hu; Xue Jiao; Jing Shi; Chenxi Li; Yanhua Li (Veterinary Research)
Abstract PRRSV nsp1α, the first viral protein translated in virus-infected cells, is released from viral polyprotein 1a through autocleavage. It plays important roles in viral replication, the suppression of the host innate immune response, and the modulation of cell-mediated immune responses. Nsp1α forms a homodimer in vitro. In this study, we aimed to elucidate the functional significance of nsp1α dimerization. Using the alanine scanning strategy, we identified valine132 and proline134 as critical residues for nsp1α dimerization. Using recombinant viruses expressing an additional FLAG-nsp1α mutant (V132A or P134A), we demonstrated that both the V132A and P134A mutations disrupted nsp1α dimerization in PRRSV-infected cells. When ectopically expressed, the V132A or P134A mutation did not affect the ability of nsp1α to antagonize host type I IFN production or degrade SLA-I molecules. Introducing V132A or P134A mutations into an HP‒PRRSV replicon system significantly interfered with the expression of a Gaussia luciferase reporter and viral proteins, suggesting that nsp1α dimerization is critical for viral replication. Using PRRSV reverse genetics, a recombinant virus carrying the V132A mutation (vV132A) was successfully rescued, while the P134A mutation was lethal. Compared with the wild-type virus, vV132A significantly attenuated growth and reduced the relative expression levels of subgenomic RNAs in MARC-145 cells. In BHK-21 cells transfected with full-length cDNA clones, the P134A mutation nearly completely blocked the synthesis of specific sgRNAs at both the minus- and positive-strand levels while maintaining sgRNA6 accumulation. Thus, nsp1α dimerization is essential for viral RNA synthesis and transcriptional regulation but appears to be dispensable for both the autoproteolytic activity and immune evasion functions of PCPα. This study not only enhances our fundamental knowledge of PRRSV biology but also establishes a foundation for developing targeted antiviral strategies against PRRSV and related arteriviruses.